Study on optimal parameter of vibration reduction system TMD-D and DVA for an inverted pendulum type structures and application to tower in the ocean - Dien, Khong Doan; Chinh, Nguyen Duy (Vietnam Journal of Mechanics, 2010)
Nguyen Dong Anh, Khong Doan Dien and Nguyen Duy Chinh in [1] have studied the vibration of inverse pendulum system installed with the vibration reduction system TMD-D and DVA. These results implemented by numerical simulation for the articulated tower in the ocean show that the obtained oscillations in some cases with installed absorber increase the amplitude of vibration when compared to the case without absorber. It is a fact that when simulation is employed, the parameters of TMD-D and DVA are chosen arbitrarily without optimal design. In the paper, the authors investigate to find the optimal parameters of the TMD-D and DVA absorbers in order to optimally reduce the vibration for the inverse pendulum system. These research results are applied to reduce the vibration for the articulated tower in the ocean.